2003
DOI: 10.1182/blood-2002-10-3089
|View full text |Cite
|
Sign up to set email alerts
|

Generation of low-toxicity interleukin-2 fusion proteins devoid of vasopermeability activity

Abstract: Because of its key role in immunity, interleukin-2 (IL-2) has been studied extensively for the adoptive immunotherapy of cancer. Although systemic administration of IL-2 has been shown to stimulate antitumor responses in vivo, its efficacy in the clinic has been limited by the development of serious side effects, including the induction of vascular leak syndrome. Previously, we have identified a small peptide fragment of IL-2 that was found to contain the entire vasopermeability activity of the cytokine. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 45 publications
(49 reference statements)
0
25
0
Order By: Relevance
“…for IL-2-mediated VLS (12,24). For anti-mouse IL-2 mAb S4B6, it is known that this mAb binds to amino acids 26-45 of mouse IL-2 (25), which overlaps with amino acids 22-31 of hIL-2 (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…for IL-2-mediated VLS (12,24). For anti-mouse IL-2 mAb S4B6, it is known that this mAb binds to amino acids 26-45 of mouse IL-2 (25), which overlaps with amino acids 22-31 of hIL-2 (26).…”
Section: Discussionmentioning
confidence: 99%
“…We measured NO 2 -in culture supernatants by using the Griess assay, as reported (24). Briefly, 1-2 × 10 5 Lin -CD31 + cells per well were left untreated or stimulated with 10 6 IU/mL IL-2.…”
mentioning
confidence: 99%
“…More recent data showed that NK cells are implicated in VLS; however, the more proximal events of endothelial cell damage and VLS include the direct binding of IL-2 to CD25 + pulmonary endothelial cells [31]. Thus, use of IL-2/ S4B6 complexes or of the IL-2 muteins R38E, R38G, R38W, and F42A (all predicted or shown to impair binding to CD25) disfavors contact with endothelial cells and significantly reduces VLS [10,31,77].…”
Section: Il-2 Muteinsmentioning
confidence: 99%
“…Thus, for exogenously-administered IL-2, renal elimination results in a very short in vivo half-life of IL-2 in the range of minutes. This has been a major limitation for IL-2-based strategies in the treatment of metastatic cancer and chronic viral infections, thus requiring the use of high doses of IL-2, which, however, can cause severe toxic side effects, termed vascular leak syndrome (11,12). In an attempt to extend in vivo halflife and increase biological activity, IL-2 has been coupled to larger proteins such as albumin and unrelated antibodies to create IL-2-IgG fusion proteins (IL-2-FP) (12,13), although with limited success.…”
Section: Il-2 Is Crucial To T Cell Homeostasis Especially Of Cd4mentioning
confidence: 99%